Predicting the nationwide outmigration timing of Atlantic salmon (Salmo salar) smolts along 12 degrees of latitude in Norway - Vollset, Knut Wiik; Lennox, Robert J.; Lamberg, Anders; Skaala, Øystein; Sandvik, Anne Dagrun; Sægrov, Harald; Kvingedal, Eli; Kristensen, Torstein; Jensen, Arne Johan; Haraldstad, Tormod; Barlaup, Bjørn Torgeir; Ugedal, Ola (Diversity and Distributions, 2021)
publishedVersion